Survival and epidemiology of amyotrophic lateral sclerosis (ALS) cases in the Chicago and Detroit metropolitan cohort: incident cases 2009–2011 and survival through 2018. Issue 3 (3rd April 2023) - Punjani, Reshma; Larson, Theodore C.; Wagner, Laurie; Davis, Bryn; Horton, D. Kevin; Kaye, Wendy
Abstract: : Amyotrophic lateral sclerosis (ALS) is a fatal, progressive neurodegenerative disorder. The National ALS Registry launched surveillance projects to understand the distribution of ALS in targeted geographic cohorts. Objective: To describe the demographics, incidence, and survival of persons with ALS (PALS) identified in the Chicago and Detroit area population-based cohort. Methods: Neurologists in the catchment area provided case reports for eligible ALS cases diagnosed and/or cared for from 1 January 2009 through 31 December 2011. Crude incidence rates were calculated for 2009–2011 and stratified by race and ethnicity. Using data from the National Death Index through 2018, we modeled the effect of patient covariates on mortality using the Cox proportional hazard regression. Results: Of the 574 cases, 372 (64.8%) were diagnosed from 2009 to 2011. The combined crude incidence rates for 2009, 2010, and 2011 were 1.44, 1.53, and 1.73 cases per 100, 000 person-years, respectively. Of the 486 subjects with complete survival data, 81% were deceased at the end of follow-up. Median survival time was 2.2 years, with 30% and 9% of subjects surviving past 5 and 10 years after diagnosis, respectively. Additionally, female PALS and PALS with longer time between symptom onset and diagnosis experienced longer survival. Nonwhites also experienced longer survival than Whites, except for those cases diagnosed in the younger age categories. Conclusion: Understanding the survival of ALS patients can aid in understanding variable prognostic factors, which can potentially extend survival and improve disease management.